O gozo de Deus: uma análise lacaniana da experiência mística na obra de Marguerite Porete - Dias, Maruzania Soares (2010)
This dissertation examines, from the perspective of Lacanian psychoanalysis, the jouissance of God in the work of Marguerite Porete, The Mirror of Simple Souls. The aim was to understand the mystical jouissance as a face of jouissance feminine and to investigate the hypothesis of the mystical jouissance in the work of Porete considered as ethical jouissance. The mystique found in this compelling book, written in the language of Courtly Love and developed as an allegory that addresses the itinerary of the protagonist Alma in her search of the perfect union with God, is sustained by the assumptions of apophatic mysticism - the dynamics of Christian mystical experience that is expressed as of empty budget. With nothing to hold her, the soul becomes nothing. The experience of mystical ecstasy allows, for a brief moment, the jouissance of God, the jouissance of this glorification, where time and eternity come together as a causeway linking the created and uncreated. By demonstrating the centrality of jouissance in the subjective economy, Lacanian psychoanalysis has established the field of jouissance and reformulated the difference between the genders providing a place that, until now, never existed for females: the logic of all-non phallic, where there is a plus-de-jouir, a jouissance that goes beyond the phallic reference. As this Other's jouissance is impossible to symbolize, we have the love as a substitute to the lack of sexual relationship between sex, given that logic Lacanian will show us that Woman does not exist 1, while universal category, which is a correlate of the enunciation there is no sexual relationship , therefore, that is no sexual proportion